Correction: Clinical Classification of Cancer Cachexia: Phenotypic Correlates in Human Skeletal Muscle - Johns, Neil; Hatakeyama, Shinji; Stephens, Nathan A.; Degen, Martin; Degen, Simone; Frieauff, Wilfried; Lambert, Christian; Ross, James A.; Roubenoff, Ronenn; Glass, David J.; Jacobi, Carsten; Fearon, Kenneth C. H.; et al. (PLOS ONE, 2024)
null